Quantum teleportation is a reversal of quantum measurement - Lee, Seung-Woo; Im, Dong-Gil; Kim, Yoon-Ho; Nha, Hyunchul; Kim, M. S. (AMER PHYSICAL SOC, 2021)
We introduce a generalized concept of quantum teleportation in the framework of quantum measurement and reversing operation. Our framework makes it possible to find an optimal protocol for quantum teleportation enabling a faithful transfer of unknown quantum states with maximum success probability up to the fundamental limit of the no-cloning theorem. Moreover, an optimized protocol in this generalized approach allows us to overcome noise in quantum channel beyond the reach of existing teleportation protocols without requiring extra qubit resources. Our proposed framework is applicable to multipartite quantum communications and primitive functionalities in scalable quantum architectures.
Keywords: ENTANGLEMENT; STATE; COMMUNICATION; PURIFICATION; COMPUTATION; NETWORK; GATE